The Effect of Employee Loyalty on Employee Work Discipline at The Department of Education and Culture of Banda Aceh City - Rizal, Syamsul; Umar, Nyak (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
The Banda Aceh City Education Office is one of the government agencies whose existence has made a very large contribution to improving education in Banda Aceh City. The purpose of this study was to determine the effect of loyalty on improving work discipline of employees of the Banda Aceh City Education Office. Loyalty is a very important element in an organization/agency to improve employee work discipline. With high loyalty from the employees, their work discipline will also increase. Based on the research results obtained, they were then processed using multiple linear regression analysis with the help of the SPSS program, so that the research results were obtained, namely: Y = 1.630 + 0.169X1 + 0.124X2 + 0.073X3 + 0.122X4 + 0.107X5 + e The results of the study showed that there was a correlation or relationship between the independent variables and the dependent variables, namely with a correlation coefficient (R) of 0.870 or 87%, which means that the two variables have a strong relationship. The magnitude of the influence of the five loyalty variables on work discipline is known by the coefficient of determination (R2) which is 0.756 or 75.6% and the remaining 24.4% is influenced by other variables outside this study. Meanwhile, based on the results of the F-test, it is known that the five loyalty variables as a whole significantly affect employee work discipline. This can be seen from the F-count which is greater than the F-table, namely 39.694> 2.358. In this study, the author used a statistical test with a confidence level of 95% (α = 0.05). Based on the description above, it can be concluded that the five loyalty variables have a significant influence on employee work discipline, which means accepting Ha and rejecting Ho, this shows that loyalty shows a positive effect on employee work discipline at the Banda Aceh City Education Office.